Social protest style in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo: stylistic studies - Sovia Wulandari; Anggi Triandana (Universitas Ahmad Dahlan, 2022)
This study aims to examine and describe Dian Purnomo's authorship style in the novel Perempuan yang Menangis kepada Bulan Hitam (PMBH) based on symbols of sexual violence against women. The use of diction, sentence style, and imagery is examined using stylistic analysis. The results of this study indicate that there are three stylistic forms, namely diction, sentence style, and imagery. Based on the results of this study, it is stated that Dian Purnomo's authorship style in the PMBH novel is in the style of Proletarian Fiction (Social Protest Fiction). Dian Purnomo, through this novel, reveals the reality that is happening in the Sumba community regarding the Marriage Catch tradition. In this tradition, many women are victims of sexual violence and hatred. Dian Purnomo prohibits protests customary rules and rulers.